Pichia anomala Induced With Chitosan Triggers Defense Response of Table Grapes Against Post-harvest Blue Mold Disease - Godana, Esa Abiso; Yang, Qiya; Zhao, Lina; Zhang, Xiaoyun; Liu, Jizhan; Zhang, Hongyin (Frontiers in Microbiology, 2021)
To study the mechanism by which Pichia anomala induced with chitosan (1% w/v) to controls the blue mold disease of table grapes caused by Penicillium expansum, changes in three yeast enzymatic activities were evaluated. Furthermore, changes in table grapes five primary disease defense-related enzymes and two non-enzyme activities were assayed. Results of the study showed that chitosan (1% w/v) significantly increased the yeast β-1,3-glucanase, catalase (CAT), and malondialdehyde (MDA) activities. Furthermore, P. anomala alone or induced with chitosan (1% w/v) significantly increased the table grapes enzymatic activities of Polyphenol oxidase (PPO), phenylalanine (PAL), peroxidase (POD), and catalase (CAT) compared to the control. The RT-qPCR results also confirmed genes of these major disease defense enzymes were up-regulated when the table grapes treated with P. anomala. The highest results recorded when the fruit treated by yeast induced with chitosan (1% w/v). The phenolic compounds, in addition to their nutritional value, can also increase the antimicrobial properties of table grapes. The current experiment determined that the total phenol and flavonoid contents of table grapes showed the highest results for fruits treated by P. anomala induced with chitosan compared with the control. Generally, the increment of these fruit enzymatic and non-enzymatic activity shows improved table grapes defense against the pathogenic fungus. Induction of the yeast with chitosan also increases its bio-control efficacy against the pathogen. Therefore, the study will enable future detailed investigation in the yeast pathogen control mechanisms to use yeasts as bio-pesticides.